2018
DOI: 10.1590/1414-431x20176867
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin inhibits cell proliferation, invasion and migration, and induces cell apoptosis in hepatocellular carcinoma

Abstract: Polydatin, a small molecule from Polygonum cuspidatum, has many biological functions, particularly anti-cancer effects. However, the anti-cancer effects of polydatin in hepatocellular carcinoma (HCC) have not been examined yet. In the present study, MTT assay, BrdU assay, transwell invasion assay, and wound healing assay were performed to determine cell proliferation, invasion and migration. Flow cytometry and TUNEL assay were used to measure cell apoptosis. Quantitative real-time PCR and western blotting assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Our findings are in agreement with a very recent study in which PD inhibited the invasion and migration of human liver cancer cells. 20 The degradation of basement membranes and stromal extracellular matrix is an essential step that leads to invasion and metastasis. MMPs are a family of human zinc-dependent endopeptidases that are responsible for degradation of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in agreement with a very recent study in which PD inhibited the invasion and migration of human liver cancer cells. 20 The degradation of basement membranes and stromal extracellular matrix is an essential step that leads to invasion and metastasis. MMPs are a family of human zinc-dependent endopeptidases that are responsible for degradation of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The root of Polygonum cuspidatum is usually formulated with several other ingredients and is most commonly prescribed for treating coughs, hepatitis, jaundice, amenorrhea, leucorrhea, arthralgia, burns, and snake bite [255]. A diversity of compounds have been isolated from Polygonum cuspidatum , dominated by resveratrol, polydatin, and anthraquinones and are presumed to be responsible for Polygonum cuspidatum 's anti-inflammatory, estrogenic, antitumour, antiaging, neuroprotective, and cardioprotective activities [256258]. In one recent in vivo study examining wound healing in rats, extracts of Polygonum cuspidatum were found to increase TGF- β 1 expression and to significantly improve wound healing in terms of reepithelization, granulation tissue formation, collagen synthesis, and angiogenesis [259].…”
Section: Traditional Use Of Medical Plants In Wound Healingmentioning
confidence: 99%
“…Additionally, PC exerts antibacterial, antiviral, and liver protection effect that can promote liver cell regeneration and recovery. Thereby, the beneficial effects of PC make it have therapeutic effect on acute hepatic ischemic injury, as evidenced by abrogated acute liver injury caused by carbon tetrachloride (CCl 4 ) [17,18]. In our study, we found that DSLHG could alleviate liver fibrosis induced by CCl 4 in rats and raised one new hopeful drug for the treatment of hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 66%